Σ-Hammett parameter: a strategy to enhance both photo- and electro-luminescence features of heteroleptic copper(i) complexes. Issue 19 (28th April 2017) - Weber, Michael D.; Viciano-Chumillas, Marta; Armentano, Donatella; Cano, Joan; Costa, Rubén D.
Abstract : Hammett was also right for devices. This work directly links the enhancement of both the photoluminescence properties in solid-state and the electroluminescence features in light-emitting electrochemical cells (LECs) with a rational ligand design using the σ-Hammett parameter. Abstract : This work studies the effect of the σ-Hammett parameter ( σ p ) – i.e., the σ-donation effect caused by substitution at the para position of a bipyridine ligand (4, 4′-R2 bipy, where R is MeO, Me, H, NO2 ) – on both the photo- and electro-luminescence features of a series of heteroleptic copper(i ) complexes – i.e., [Cu(N^N)(P^P)] + where N^N and P^P ligands are R2 bipy and Xantphos, respectively. By virtue of a comprehensive photophysical, theoretical, and thin-film lighting device – i.e., light-emitting electrochemical cells (LECs) – investigation, we note a clear relationship between the σ p and the photo- and electro-luminescence parameters, such as photoluminescence quantum yields, excited-state lifetimes, and emission maxima, as well as device brightness, stability, and efficacy, respectively. As the most relevant finding, the substitution with the group featuring the most negative σ p – i.e., MeO – provides a ca . five-fold enhancement of all of the aforementioned figures-of-merit upon comparison within the series of complexes. As such, this work provides a new guideline for a device optimization through a rational ligand design for heteroleptic copper(i ) complexes.